Recent Advances in Phytoleads for Management of Respiratory Disorders - Jain, Sameeksha (International Journal of Pharmaceutical & Biological Archive, 2023)
Respiratory disorder is one of the common disorders related to the respiratory tract. In regards, to the development of resistance against the drugs now in use, respiratory disorders become a significant major challenge in the health sector. For respiratory illness treatment, many phytoleads or phytoconstituents are traditionally used and for their efficacy, few have been found with optimistic results. In this review, all the phytoleads or phytoconstituents have anti-inflammatory activity, and some of them possess antioxidant activity too. All are used to treat respiratory tract inflammation. Curcumin was used as an anti-asthmatic also. The results of this study show that for the cure of respiratory system disorders, phytoleads or phytoconstituents are used.The use of Phytoleads nowadays provide benefit in the discovery of new drugs for future targets.